2012
DOI: 10.2147/jpr.s33453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of XaraColl®, a bupivacaine-collagen implant, for postoperative analgesia in two multicenter, randomized, double-blind, placebo-controlled pilot studies

Abstract: BackgroundXaraColl®, a collagen-based implant that delivers bupivacaine to the site of surgical trauma, is under development for postoperative analgesia. Because of differing patient attitudes to postoperative pain control and the inability to assess baseline pain, standard clinical methods for evaluating analgesic efficacy are compromised and justify application of novel integrated approaches.MethodsWe conducted two independent, multicenter, double-blind, placebo-controlled studies in men undergoing unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Thereafter, there is a slow release phase which can sustain the local concentrations and provide analgesia through at least 48 hours. Such a mechanism is consistent with results from our controlled efficacy trials that have demonstrated analgesia through 72 hours postoperatively in patients undergoing open inguinal hernioplasty and gynecological surgeries 3,4…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thereafter, there is a slow release phase which can sustain the local concentrations and provide analgesia through at least 48 hours. Such a mechanism is consistent with results from our controlled efficacy trials that have demonstrated analgesia through 72 hours postoperatively in patients undergoing open inguinal hernioplasty and gynecological surgeries 3,4…”
Section: Discussionsupporting
confidence: 88%
“…Other products currently in development include Posidur ® (Durect Corporation, Cupertino, CA), an injectable viscous depot of bupivacaine based on sucrose acetate isobutyrate, and XaraColl ® (Innocoll Technologies, Athlone, Ireland) (Figure 1), a biodegradable and fully resorbable collagen-based matrix that is designed to release and deliver bupivacaine for local, sustained action at the site(s) of surgical trauma. Randomized controlled trials performed in women undergoing open gynecological surgery3 and in men undergoing hernioplasty4 have concluded that XaraColl is effective in reducing patient use of opioid analgesia and/or their pain intensity for up to 3 or 4 days postoperatively. The product also offers great versatility and is already proven suitable for use in laparoscopic surgery 5.…”
Section: Introductionmentioning
confidence: 99%
“…Since this was not a controlled study, we compared values of TOpA and SPI with previously reported pooled data from two studies of men undergoing open inguinal hernioplasty who also had the benefit of receiving XaraColl for postoperative analgesia 9. After 24 hours, the mean TOpA for this laparoscopic study (19.3 mg) was very similar to the value from the pooled open hernioplasty studies (19.5 mg).…”
Section: Resultsmentioning
confidence: 71%
“…We have recently reported on the safety and efficacy of XaraColl, a bupivacaine-collagen implant, for postoperative analgesia in patients undergoing open inguinal hernioplasty9 and open gynecological surgery 10. From the results obtained, we concluded that XaraColl implanted intraoperatively was able to target and control visceral pain more efficiently than continuous perfusion of the surgical wound with bupivacaine for 72 hours postoperatively 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation